2018
DOI: 10.1177/1090198118769357
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Youth Participatory Action Research (YPAR) in the United States: Methodologies, Youth Outcomes, and Future Directions

Abstract: This systematic review provides emerging evidence of the skills and competencies youth may develop through YPAR and offers methodological recommendations for future research that can provide greater evidence of causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
268
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 305 publications
(284 citation statements)
references
References 74 publications
14
268
0
2
Order By: Relevance
“…During this dissemination component, youth researchers often presented with PowerPoint and spoke publicly to share their results, typically with adults outside of the project. This aligns with a prior review of YPAR outcomes, which found that the method of social action most often took the form of education and awareness (Anyon et al., ). As a result, adult researchers should consider how to leverage these presentation opportunities to increase youth researchers’ access to stakeholders across a variety of contexts and to provide a platform for youth researchers’ expertise to be shared.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…During this dissemination component, youth researchers often presented with PowerPoint and spoke publicly to share their results, typically with adults outside of the project. This aligns with a prior review of YPAR outcomes, which found that the method of social action most often took the form of education and awareness (Anyon et al., ). As a result, adult researchers should consider how to leverage these presentation opportunities to increase youth researchers’ access to stakeholders across a variety of contexts and to provide a platform for youth researchers’ expertise to be shared.…”
Section: Resultssupporting
confidence: 82%
“…With YPAR's epistemological foundation and the present considerations for pedagogy and stakeholder dynamics in mind, adult researchers and educational advocates should carefully consider implementing YPAR in high school settings as a possible avenue to shift notions of knowledge construction to youth who occupy those settings (Caraballo et al., ). The demonstrated benefits to youth across academic, social, and leadership domains (Anyon et al., ; Shamrova & Cummings, ) show that YPAR is a worthwhile mode of inquiry in school settings. Indeed, when grounded in YPAR's epistemological foundation, YPAR in high school settings has the potential to subvert traditional educational paradigms by legitimizing students’ experiences and knowledge (Freire, ; Caraballo et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in academic performance emerges in studies 1 and 2. In a systematic review of YPAR programs, author Anyon and colleagues [38] corroborates the impacts of these programs on the promotion of academic competencies, contrarily to the study of Voight and Velez [32] developed in a school context.…”
Section: Discussionmentioning
confidence: 88%